2021
DOI: 10.1152/ajprenal.00015.2021
|View full text |Cite
|
Sign up to set email alerts
|

Actin-related protein 2/3 complex plays a critical role in the aquaporin-2 exocytotic pathway

Abstract: The trafficking of proteins such as aquaporin-2 (AQP2) in the exocytotic pathway requires an active actin cytoskeleton network, but the mechanism is incompletely understood. Here, we show that the actin-related protein (Arp) 2/3 complex, a key factor in actin filament branching and polymerization, is involved in the shuttling of aquaporin-2 (AQP2) between the trans Golgi network (TGN) and the plasma membrane. Arp2/3 inhibition (using CK-666) or siRNA knockdown blocks vasopressin induced AQP2 membrane accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Cellular responses to these external cues are regulated intracellularly through numerous signaling cascades, which include the Rho family of small GTPases and their downstream protein kinase effectors. Arp2/3 complex is a key factor in actin filament branching and polymerization, essential for dendritic spine structural plasticity and stability (54) which was upregulated in LSD exposed organoids. LSD also modulated Rho GTPase CDC42, the protein kinase PAK1, and WASF1, a member of the actin regulatory WAVE complex.…”
Section: Resultsmentioning
confidence: 99%
“…Cellular responses to these external cues are regulated intracellularly through numerous signaling cascades, which include the Rho family of small GTPases and their downstream protein kinase effectors. Arp2/3 complex is a key factor in actin filament branching and polymerization, essential for dendritic spine structural plasticity and stability (54) which was upregulated in LSD exposed organoids. LSD also modulated Rho GTPase CDC42, the protein kinase PAK1, and WASF1, a member of the actin regulatory WAVE complex.…”
Section: Resultsmentioning
confidence: 99%
“…The actin-related protein (Arp)2/3 complex is a key factor in actin filament branching and polymerization. Inhibition of the Arp2/3 complex has been shown to prevent AQP2 exocytosis [ 52 ]. Using 3D super-resolution microscopy, Holst et al reported that association of AQP2-containing vesicles with F-actin is enhanced by serine 256 phosphorylation [ 53 ].…”
Section: The Role Of the Cytoskeleton In Aqp2 Traffickingmentioning
confidence: 99%
“…Together, these data suggest that phosphorlyation of AQP2 alters local actin dynamics by altering the concentrations of G-actin and TM5b, in order to locally disrupt the cortical actin network and provide a path to the membrane for AQP2-bearing vesicles. Recently it has been suggested that the Arp2/3 complex, which generates nucleation sites for actin filament branching, is required for AQP2 exit from the trans-Golgi network [64] , [65] , but the mechanism is not yet understood.…”
Section: Introductionmentioning
confidence: 99%